2016
DOI: 10.1002/cctc.201600372
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for the Characterization of Lewis Acidic Solid Catalysts by Solid‐State NMR Spectroscopy

Abstract: Acetone‐2‐13C, trimethylphosphine oxide (TMPO), and ammonia were applied as probe molecules for solid‐state NMR investigations of Lewis acid sites on γ‐Al2O3, TiO2/anatase, and lithium‐exchanged zeolite Na‐Y. An indication for Lewis acid sites are the 31P MAS NMR signals at 48–51 ppm for TMPO‐loaded catalysts. The determination of the Lewis site density through the evaluation of these 31P MAS NMR signals, however, is difficult owing to the demanding TMPO adsorption procedure. Upon ammonia adsorption, the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 31 publications
3
60
0
Order By: Relevance
“…More recently, Lang et al performed a systematic study of alumina and metal-exchanged zeolites using various probe molecules, such as 2-13 C-acetone, TMPO, and ammonia. [32] By comparison with the results of other probe molecules, these authors suggested that adsorption of ammonia on LAS causes 1 H MAS NMR signals in the chemical shift range of δ 1H = À 0.5 to 3.0 ppm, which agrees well with the current observation of ammonia adsorbed on LAS in ASAs.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…More recently, Lang et al performed a systematic study of alumina and metal-exchanged zeolites using various probe molecules, such as 2-13 C-acetone, TMPO, and ammonia. [32] By comparison with the results of other probe molecules, these authors suggested that adsorption of ammonia on LAS causes 1 H MAS NMR signals in the chemical shift range of δ 1H = À 0.5 to 3.0 ppm, which agrees well with the current observation of ammonia adsorbed on LAS in ASAs.…”
Section: Resultssupporting
confidence: 81%
“…This signal is accompanied by strong and broad spinning sidebands, which was not observed with SiOH groups or BAS. The strong and broad sidebands indicate that ammonia molecules are strongly adsorbed on these surface sites, i. e. on surface LAS via electron pairs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increase of the broad autocorrelation signal at (2.6, 5.2) ppm with increasing Al/Si ratio from 1/9 to 5/5 (compare Fig. 1d and Supplementary Note 2) allows assigning it to ammonia adsorbed on LAS [51][52][53][54] . Such assignment is supported by previously reported 2D 27 Al-1 H through-space correlations of SA/10 and SA/50 loaded with ammonia 16 .…”
Section: Articlementioning
confidence: 99%
“…Both signals are attributed to the high content of Al cations, particularly, three‐coordinate Al 3+ species as revealed in the above 27 Al MAS NMR study. Notably, the assignment of the signal at δ 31P =37 ppm was considered as TMPO at LAS by Rakiewicz et al., however, was not observed with TMPO‐loaded γ‐Al 2 O 3 . According to Zheng et al .…”
Section: Resultsmentioning
confidence: 99%